Spirometry in Primary Care - Allan L Coates; Brian L Graham; Robin G McFadden; Colm McParland; Dilshad Moosa; Steeve Provencher; Jeremy Road (Canadian Respiratory Journal)
Canadian Thoracic Society (CTS) clinical guidelines for asthma and chronic obstructive pulmonary disease (COPD) specify that spirometry should be used to diagnose these diseases. Given the burden of asthma and COPD, most people with these diseases will be diagnosed in the primary care setting. The present CTS position statement was developed to provide guidance on key factors affecting the quality of spirometry testing in the primary care setting. The present statement may also be used to inform and guide the accreditation process for spirometry in each province.